Technology, decoupling, and ecological crisis: examining ecological modernization theory through patent data. Issue 2 (3rd April 2022) - Bugden, Dylan
ABSTRACT: Ecological modernization refers to the process of resolving ecological crises through radical improvements in resource efficiency and the substitution of environmentally harmful industrial processes for less harmful ones without undermining economic growth and other capitalist imperatives. An important theoretical perspective within environmental sociology, it is also the intellectual kin of global environmental policies that pursue objectives such as decoupling, green growth, and sustainable development. While numerous studies cast doubt on ecological modernization and its associated policy efforts, existing empirical analyses do not fully address the theory's core hypothesis on the relationship between technological innovation and environmental impacts. I resolve this problem by using newly available global patent data on environmental technologies across 35 countries from 1982–2016. Results of panel regression analyses demonstrate that a nation's development of environmental technologies only marginally attenuates the effects of economic activity on a nation's ecological footprint, while the direct effect of patents is to increase, rather than decrease, a nation's ecological footprint. These results offer further evidence of the limits of both (a) ecological modernization theory and (b) environmental policies that exclusively emphasize technological solutions to global environmental problems.